Topical (pour-on) ivermectin in the treatment of canine scabies. - Paradis, M (1997)
The efficacy of a pour-on formulation of ivermectin at 500 micrograms/kg body weight applied on the dorsum on days 1 and 15 was evaluated in 90 dogs from a shelter, naturally infested with Sarcoptes scabiei. This very practical form of treatment was successful in eradicating scabies from this shelter.